Effects of Barents–Kara Seas ice and North Atlantic tripole patterns on Siberian cold anomalies - Yanan Chen; Dehai Luo; Linhao Zhong; Yao Yao (Weather and Climate Extremes, 2021)
Possible physical routes are presented that link the decline in sea-ice concentration (SIC) in the Barents–Kara Seas (BKS), the sea surface temperature anomaly in the pattern of the North Atlantic tripole (NAT), and the Siberian cold anomaly in boreal winter, via mid–high-latitude circulation anomalies mainly characterized by Ural blocking (UB). It is found that the Siberian cold anomalies with BKS SIC loss are mostly related to UB, while those without significant BKS SIC loss are significantly correlated with the North Atlantic Oscillation (NAO). The negative/positive-phase NAT (NAT−/NAT+) exerts its impact on the cold/warm anomalies over northern Eurasia through coupling with the negative/positive-phase NAO (NAO−/NAO+). In particular, a strong NAT− winter tends to cause a cold anomaly shifting southwards from the polar area to mid–high-latitude of Eurasia, producing a severe cold event over Siberia. From the perspective of intraseasonal atmospheric circulation, a UB event under NAT− winter leads to a more intense Siberian cold anomaly than one under NAT+, suggesting a vital role played by the NAO in forming cold conditions in Siberia. Considering the effects of BKS sea-ice variation, it is revealed that the UB-related Siberian cold anomaly tends to achieve its maximum strength in a NAT− winter when the BKS SIC declines. However, for winters with sea ice loss in BKS but a weak NAT+, the UB-related Siberian cold anomaly shows southward displacement. It is also found that strong NAT− coupling with a strong NAO− can cause cold conditions in Siberia without the need for a BKS SIC decline and long-lived UB, and this explains 75% of the cold Siberian winters in the context of increased BKS SIC.